Congenital chylothorax managed with octreotide and skimmed milk: a case report - Sandhu, Jaskirat Kaur; Kaur, Satpreet (International Journal of Contemporary Pediatrics, 2023)
Pleural effusion occurs when a large amount of free fluid accumulates in the pleural space. A chylothorax is caused by chyle-containing lymphatic fluid draining into the pleural cavity. This is the most common type of pleural effusion observed during the neonatal period. It causes a number of respiratory and nutritional issues and has a significant mortality rate. It is usually treated by intercostal chest tube drainage and total parenteral nutrition. Octreotide is a relatively newer strategy in the management. Here we describe the case of a 16 days old male neonate who presented to us with sudden onset severe respiratory distress requiring invasive ventilation. Radiology suggested pleural effusion and so intercostal chest tube was inserted, which revealed Chylous effusion. The patient was successfully managed with dietary therapy including skimmed milk and octreotide infusion.